The global workspace needs metacognition - Shea, N; Frith, C (Cell Press, 2019)
The two leading cognitive accounts of consciousness currently available concern global workspace (a form of working memory) and metacognition. There is relatively little interaction between these two approaches and it has even been suggested that the two accounts are rival and separable alternatives. Here, we argue that the successful function of a global workspace critically requires that the broadcast representations include a metacognitive component.